Ubiquitin–proteasome system-targeted therapy for uveal melanoma: what is the evidence? - Zhao, Chen-xi (Acta Pharmacol Sin, 2020)
Uveal melanoma (UM) is a rare ocular tumor. The loss of BRCA1-associated protein 1 (BAP1) and the aberrant activation of G protein subunit alpha q (GNAQ)/G protein subunit alpha 11 (GNA11) contribute to the frequent metastasis of UM. Thus far, limited molecular-targeted therapies have been developed for the clinical treatment of UM. However, an increasing number of studies have revealed the close relationship between the ubiquitin proteasome system (UPS) and the malignancy of UM. UPS consists of a three-enzyme cascade, i.e. ubiquitin-activating enzymes (E1s); ubiquitin-conjugating enzymes (E2s); and ubiquitin-protein ligases (E3s), as well as 26S proteasome and deubiquitinases (DUBs), which work coordinately to dictate the fate of intracellular proteins through regulating ubiquitination, thus influencing cell viability. Due to the critical role of UPS in tumors, we here provide an overview of the crosstalk between UPS and the malignancy of UM, discuss the current UPS-targeted therapies in UM and highlight its potential in developing novel regimens for UM.